Eit Performance Criteria According to Variations in Conductivity - Sepulveda-Palma, F (Springer Science and Business Media Deutschland GmbH, 2022)
Multiphase flow measurements allow monitoring and control of flows in real time. The extraction of oil in new fields has resulted in the demand for technologies capable of acting in extreme conditions, such as the high conductivity of saline water. Conductivity variation can impact EIT image reconstruction, and an alternative to ensure image reconstruction is to make online calibration viable. To support online calibration solutions, the study of the impact of conductivity on performance criteria can contribute to safety and control. Therefore, this article aims to assess the behavior of EIT performance criteria according to variations in conductivity, through the analysis of the conductivity effects on measurement errors, through the most common indexes for the analysis of measurement errors, for example, signal-to-noise ratio (SNR), and reciprocity error (RE). Through this study, it is possible to observe that in low concentrations, it is necessary to increase the signal conditioning gain according to the behavior of the solution conductivity. After a specific concentration, the conductivity stabilizes, and there is no need to adjust the gain. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.